Patella fractures treated with cannulated lag screws and fiberwire® have a high union rate and low rate of implant removal. Issue 2 (February 2020) - Busel, Gennadiy; Barrick, Brett; Auston, Darryl; Achor, Kyle; Watson, David; Maxson, Ben; Infante, Anthony; Sanders, Roy; Mir, Hassan R.
Highlights: Hardware irritation is a major cause for reoperation in fixation of patella fractures. Suture cerclage is a powerful adjunct to the screw fixation of the transverse patella fracture without increase rate in hardware irritation. This leads to lower levels of hardware removal. High union rate is expected with utilization of the suture cerclage in treatment of transverse patella fractures. Abstract: Objectives: The purpose of this study is to report the results of open reduction internal fixation of patella fractures (OTA 34 A-C) using cannulated lag screws and FiberWire® (Arthrex, Naples, FL, USA) with regard to union and symptomatic implant removal. Design: Retrospective review of prospectively collected database. Setting: Urban Level 1 trauma center and Level 2 trauma center Methods: All displaced intra-articular patella fractures (OTA 34 A-C) treated with ORIF by cannulated lag screws and FiberWire® tension band/cerclage between January 1, 2009 and August 1, 2018. Three hundred and eighty seven consecutive patients were identified. Fifty fractures were included in the final analysis. Main Outcome Measurement: All patients were followed to clinical and radiographic union. Nonunion was defined as lack of clinical and radiographic union, fracture displacement, and/or return to OR for revision surgery. Rate of symptomatic implant removal was recorded. Results: Average age was 57.7 years (range 21–86). Average follow up was 20.6 months (range 6–98 months). Average time to clinical and radiographic union was 3.1 months (range 3–7 months). Four fractures were open. There was a 96% (48/50) rate of primary union, with one patients requiring revision surgery to achieve union, and one developing an asymptomatic radiographic nonunion. The rate of symptomatic implant removal was 8% (4/50). Only 1 of the 4 was operated for a prominent suture knot, and the remaining 3 were for prominent screw removal. Knee range of motion averaged 0.37° extension to 119° flexion (range, 0–150°). Conclusion: Patella fractures can be treated with cannulated lag screws and FiberWire® with a high rate of primary union (96%) and a low rate of symptomatic implant removal (8%). The implant removal rate compares favorably with alternative constructs, with an equivalent rate of fracture union.